2018
DOI: 10.3168/jds.2017-12930
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of variability between competitively fed dairy cows through increased feed delivery frequency

Abstract: The objective of this study was to determine whether increased frequency of total mixed ration (TMR) delivery could mitigate the effects of feed bunk competition on the behavior and productivity of individual lactating dairy cows within a group. We hypothesized that, for competitively fed cows, a greater frequency of TMR delivery would improve access to feed, and reduce individual variability in behavior, meal patterns, and production between cows. Sixteen lactating Holstein dairy cows (first lactation = 4, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 48 publications
4
14
1
3
Order By: Relevance
“…For instance, the space allowance per strip for 7A cows ranged from 5.6 to 22.8 m 2 per cow, whereas the minimum recommended space allowance for beef cattle in Australian feedlots is 9 m 2 per cow [ 46 ]. In cattle, high social rank is associated with age [ 47 , 48 ], weight [ 47 ], and, when fed grain competitively, intake [ 37 , 47 , 49 ]. Stafford and Gregory [ 8 ] warned that increased intensification of grazing management may pose risks to the welfare of grazed cattle, particularly for animals of lower social status who could be forced away from fresh pasture [ 8 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the space allowance per strip for 7A cows ranged from 5.6 to 22.8 m 2 per cow, whereas the minimum recommended space allowance for beef cattle in Australian feedlots is 9 m 2 per cow [ 46 ]. In cattle, high social rank is associated with age [ 47 , 48 ], weight [ 47 ], and, when fed grain competitively, intake [ 37 , 47 , 49 ]. Stafford and Gregory [ 8 ] warned that increased intensification of grazing management may pose risks to the welfare of grazed cattle, particularly for animals of lower social status who could be forced away from fresh pasture [ 8 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crossley et al (2017) reported that when dairy cows competed for access to a feeding area, there was an increase in variability in feeding time, feeding rate and meal duration. In a companion study, increasing feeding frequency did not reduce variability in feeding time, feeding rate or dry matter intake (Crossley et al, 2018). This variability is likely due to individual motivations to access the feed bunk; some animals reduce feeding time and others strive to maintain feeding times even under high levels of competition (dairy cattle: Val-Laillet et al, 2008b;goats: Jørgensen et al, 2007).…”
Section: Expression Of Feeding Behaviourmentioning
confidence: 98%
“…A meal bout was defined as at least one observation of eating activity occurring after at least 20 min without eating activity (Wangsness et al, 1976). Meal size (kg of DM/ meal) was calculated as DMI divided by meal frequency (Crossley, Harlander-Matauschek, & DeVries, 2018). The total chewing time was calculated as the sum of ruminating and eating time, and the number of chews per bolus was enumerated during each rumination period for each cow.…”
Section: Feeding Behaviourmentioning
confidence: 99%